Clinical case of successful surgical treatment of arteriovenous malformation of the thumb finger - A. R. Rakhimov; D. V. Romanov; M. A. Karev (Амбулаторная хирургия)
The management of arteriovenous malformations of the hand is one of the most difficult problems in vascular surgery. It’s primarily related to the number of vessels and nerves involved in the pathological process on a very limited anatomical area. Commonly the required steps of the diagnostic process are the following: clinical examination, Doppler colour flow mapping, MRI with intravenous contrast, angiography and thermography. There are various methods ofsurgical treatment of patients with arteriovenous malformation of the hand. Generally, they might be classified as endovascular and open-surgical ones. Endovascular methods, such as embolization and sclerotherapy, are associated with the risk of severe complications such as soft tissue necrosis, distal vascular bed-specific thrombosis, along with both sensory and motor connectivity of the hand. However minimally invasive procedures do not always contribute to an appropriate clinical result. This article presents an example of successful surgical treatment of a patient with arterio-venous malformation of the thumb finger with severe pain syndrome and recurrent bleeding ulcers. A radical removal of the malformation-bearing tissue with preservation of the arterial blood supply was performed under an arterial tourniquet. At the one-year post-surgery follow-up examination, the patient noted the absence of pain syndrome and ulcers, restoration of mobility in the interphalangeal and metacarpophalangeal joints. Thus, the treatment of arteriovenous malformation of the hand should be based on the latest research findings and the most advanced testing technologies. This clinical case demonstrates that open surgery can be considered as an effective and sustainable clinical approach with a good medium-term outcome for the patients with arteriovenous malformation of the hand.